2021
DOI: 10.1007/s40192-021-00239-y
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Glass Forming Ability of Bulk Metallic Glasses Using Machine Learning

Abstract: Bulk metallic glass has been a fascinating class of metallic systems with remarkable corrosion resistance, elastic modulus, and wear resistance, while evaluating the glass forming ability has been a very interesting aspect for decades. Machine learning techniques, viz., artificial neural networks and KNearest Regressor-based models have been developed in this work to predict the glass forming ability, given the composition of the bulk metallic glassy alloy. A new criterion of classification of atoms present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Mastropietro et al used multiple linear regression and tree boosting to predict the maximum amorphous diameter of Fe-based BMGs; the R 2 value was increased from 0.71 to 0.90 after training [69]. Reddy et al predicted the glass-forming ability of a BMG by ML based on elemental composition alone [70]. Schultz et al tried to link characteristic temperature and glassforming ability in BMGs by ML; it was found that the critical cooling rate (R c ) might be a better target for machine learning model prediction than critical casting diameter (D c ) [71].…”
Section: Potential Composition Design Methods For Heaasmentioning
confidence: 99%
“…Mastropietro et al used multiple linear regression and tree boosting to predict the maximum amorphous diameter of Fe-based BMGs; the R 2 value was increased from 0.71 to 0.90 after training [69]. Reddy et al predicted the glass-forming ability of a BMG by ML based on elemental composition alone [70]. Schultz et al tried to link characteristic temperature and glassforming ability in BMGs by ML; it was found that the critical cooling rate (R c ) might be a better target for machine learning model prediction than critical casting diameter (D c ) [71].…”
Section: Potential Composition Design Methods For Heaasmentioning
confidence: 99%
“…In the model, the elements from a given set and final required phases of HEA are taken as the input parameters and then, the algorithm, through a combination of ML models (HEA classifier and BM regressor), predicts the most favourable elemental composition to optimize the bulk-modulus for the HEA. The HEA classifier was trained by using data from the research work of Dam et al 29 and Reddy et al 30 . The data used for the prediction of bulk modulus values for the HEA cluster was taken from Precker et al 31 and Mishra et al 32 .…”
Section: Pre-processingmentioning
confidence: 99%
“…These approaches enable researchers to develop models that can accurately predict the GFA of new compositions, thereby reducing the need for extensive experimentation. Currently, most GFA predictions are based on estimating the critical diameter (D max ) [6][7][8][9][10][11][12][13]. While D max provides a direct measure of GFA, it is influenced by various factors, including fabrication processes, sample shape, and testing methods.…”
Section: Introductionmentioning
confidence: 99%